2020
DOI: 10.1155/2020/3718305
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Analysis of Castleman’s Disease of the Lacrimal Gland

Abstract: Objective. To explore the clinical manifestations, imaging characteristics, and pathological characteristics of Castleman’s disease of the lacrimal gland, enhance the knowledge of the disease, and improve the level of its diagnosis and treatment. Methods. In the retrospective study, the data of 5 patients diagnosed with Castleman’s disease of the lacrimal gland in Tianjin Medical University Eye Hospital from 2014 to 2018 were analyzed, and the relevant literature was reviewed. Results. All the 5 patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…MCD is a systemic lymphoproliferative disorder that can lead to mass lesion formation in various parts of the body, including the lungs, kidneys, and extranodal sites. Although orbital tissue involvement is relatively rare due to the lack of lymphatic components, previous cases of MCD affecting the lacrimal gland have been reported [ 8 , 9 ]. Venizelos et al reported that orbital involvement might be the initial clinical presentation of CD and those with unicentric hyaline-vascular CD cases showed no association with systemic symptoms and were rarely recurrent [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…MCD is a systemic lymphoproliferative disorder that can lead to mass lesion formation in various parts of the body, including the lungs, kidneys, and extranodal sites. Although orbital tissue involvement is relatively rare due to the lack of lymphatic components, previous cases of MCD affecting the lacrimal gland have been reported [ 8 , 9 ]. Venizelos et al reported that orbital involvement might be the initial clinical presentation of CD and those with unicentric hyaline-vascular CD cases showed no association with systemic symptoms and were rarely recurrent [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Commonly affected areas include the mediastinum, the axillary and inguinal regions, as well as the abdominal cavity [8]. Case reports have also highlighted extranodal incidents of CD; namely, in the pancreas, the lacrimal glands, and intramuscularly [7,[11][12][13]. Constitutional symptoms in UCD are rare and, when present, give rise to suspicions of other clinical entities, rather than CD [4].…”
Section: Discussionmentioning
confidence: 99%